2019
DOI: 10.1089/ct.2019;31.195-197
|View full text |Cite
|
Sign up to set email alerts
|

Mild-to-Moderate Iodine Deficiency in Early Pregnancy Is Associated with Lower Verbal IQ in Children

Abstract: BackgroundSevere maternal iodine deficiency is known to be associated with low offspring IQ (1). However, the effects of mild-to-moderate maternal iodine deficiency on child neurocognitive outcomes remain poorly understood, and results of cohort studies have been somewhat variable (2-5). The effects of maternal iodine status at different gestational ages on child neurodevelopment have not been examined previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…This notion that mild-to-moderate GID selectively affects verbal IQ was also identified in a recent meta-analysis [35,36] based on data from three European pregnancy cohorts: Generation R in the Netherlands [37], the INfancia y Medio Ambiente Project (INMA) in Spain [38] and the already discussed ALSPAC study [21]. Summarizing this meta-analysis, it was reported that lower urinary iodine-to-creatinine ratios up to week 14 of gestation were associated with poorer verbal IQ scores (mean 6 IQ points difference across the three cohort studies), but there was no association of maternal iodine status with children’s non-verbal IQ scores.…”
Section: The Avon Longitudinal Study Of Parents and Children (Alspmentioning
confidence: 53%
“…This notion that mild-to-moderate GID selectively affects verbal IQ was also identified in a recent meta-analysis [35,36] based on data from three European pregnancy cohorts: Generation R in the Netherlands [37], the INfancia y Medio Ambiente Project (INMA) in Spain [38] and the already discussed ALSPAC study [21]. Summarizing this meta-analysis, it was reported that lower urinary iodine-to-creatinine ratios up to week 14 of gestation were associated with poorer verbal IQ scores (mean 6 IQ points difference across the three cohort studies), but there was no association of maternal iodine status with children’s non-verbal IQ scores.…”
Section: The Avon Longitudinal Study Of Parents and Children (Alspmentioning
confidence: 53%
“…Since thyroid hormone (TH) is involved early first trimester fetal brain development including the proliferation, migration, and differentiation of neuronal cells [7][8][9], it is expected that developmental neuronal defects cannot be totally reversed postnatally. These irreversible changes can impact on child IQ, cognitive and motor measures [2,5,[13][14][15][16]. Children affected may present reduced socio-educational achievement [17,18], greater risk of autistic trait [14], and more ADHD (attention-deficit/hyperactivity disorder) symptoms [19].…”
Section: Current Neonatal Screening Of Thyroid Function and Chtmentioning
confidence: 99%